Life Satisfaction in Students: The Relationship of Social Support and School Climate - Rima Wilantika; Nurul Hidayah (Fakultas Ushuluddin, Adab dan Dakwah - Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2024)
This study aims to determine how social support and school climate predict life satisfaction of vocational high school students. The research participants were vocational high school students in Pringsewu, with the number of subjects used in the study being 200 students. The instruments in this study consisted of a scale of life satisfaction, social support, and school climate. The analytical method used was multiple regression analysis with the help of the SPSS version 23 program. The results of the data analysis between social support and school climate with life satisfaction showed a significance value of the R coefficient of 0.000, meaning that simultaneously social support and school climate were able to predict high and low levels of life satisfaction. Meanwhile, separately, between social support and life satisfaction showed a significance value of the zero-order coefficient of 0.001 and between school climate and life satisfaction showed a significance value of the zero-order coefficient of 0.015; meaning that between social support and life satisfaction, there was a significant relationship, as well as between school climate and life satisfaction. The conclusion in this study is that, both simultaneously and separately, social support and school climate were able to predict student life satisfaction.